2018
DOI: 10.1175/jcli-d-18-0108.1
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Relationship among Metrics of Tropical Expansion

Abstract: There is mounting evidence that the width of the tropics has increased over the last few decades, but there are large differences in reported expansion rates. This is, likely, in part due to the wide variety of metrics that have been used to define the tropical width. Here we perform a systematic investigation into the relationship among nine metrics of the zonal-mean tropical width using preindustrial control and abrupt quadrupling of CO2 simulations from a suite of coupled climate models. It is shown that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
132
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(148 citation statements)
references
References 26 publications
7
132
0
Order By: Relevance
“…The lack of correlations between the latitudes of the STJ and EDJ has been shown previously (Davis & Birner, 2017;Solomon et al, 2016;Waugh et al, 2018), and correlations between metrics of the jets are shown in Figure S2 of the supporting information. The lack of correlations between the latitudes of the STJ and EDJ has been shown previously (Davis & Birner, 2017;Solomon et al, 2016;Waugh et al, 2018), and correlations between metrics of the jets are shown in Figure S2 of the supporting information.…”
Section: Interannual Variabilitysupporting
confidence: 56%
See 2 more Smart Citations
“…The lack of correlations between the latitudes of the STJ and EDJ has been shown previously (Davis & Birner, 2017;Solomon et al, 2016;Waugh et al, 2018), and correlations between metrics of the jets are shown in Figure S2 of the supporting information. The lack of correlations between the latitudes of the STJ and EDJ has been shown previously (Davis & Birner, 2017;Solomon et al, 2016;Waugh et al, 2018), and correlations between metrics of the jets are shown in Figure S2 of the supporting information.…”
Section: Interannual Variabilitysupporting
confidence: 56%
“…In all models there is a poleward movement of HC and EDJ in response to 4xCO 2 , there is a high correlation in the HC and EDJ response across models, and the slope of the linear fit between change across models is close to the multimodel mean regression coefficient for interannual variations in the piControl runs (see Figure 8 of Waugh et al, 2018). Note that this contrasts the consistencies between the HC edge and EDJ latitude responses.…”
Section: Forced Responsementioning
confidence: 72%
See 1 more Smart Citation
“…The climate in the tropics and subtropics is often described as being dominated by the meridional overturning Hadley circulation (HC). The HC is observed to be widening by about 0.2° per decade in each hemisphere since 1979 (S. M. Davis & Rosenlof, ; Fu et al, ; Grise et al, ; Y. Hu & Fu, ; Seidel & Randel, ; Seidel et al, ; Staten et al, ), and both theory and models suggest that this widening will continue during the coming century as a result of continued greenhouse gas (GHG) concentration increases (Chen et al, ; D ' Agostino & Lionello, ; Kim et al, ; Min & Son, ; Nguyen et al, ; Staten et al, ; Waugh et al, ). With over 1 billion people (~17% of Earth's human population) living within ±3° of the present HC edges (Doxsey‐Whitfield et al, ), diagnosing the underlying circulation dynamics associated with recent projections of subtropical aridification (Cook et al, ; Karnauskas et al, , ; Scheff & Frierson, ) is a timely challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods for defining the regional extent of the tropics include outgoing longwave radiation thresholds, sea level pressure (SLP) maxima, and tropopause‐based metrics. But outgoing longwave radiation is affected not only by changes in the tropical circulation but also by thermodynamic changes and is thus a poor measure of variability and change in the tropical overturning circulation, at least in the zonal mean (Waugh et al, ). The SLP changes associated with the HC are strongest over oceans (Schmidt & Grise, ), even though the tropical overturning circulation has clear impacts over both land and ocean (Chen et al, ; Freitas et al, ; Huang et al, ; Lucas & Nguyen, ; Zhao & Moore, ).…”
Section: Introductionmentioning
confidence: 99%